The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/foods10020225
|View full text |Cite
|
Sign up to set email alerts
|

Sensorial, Melissopalynological and Physico-Chemical Characteristics of Honey from Babors Kabylia’s Region (Algeria)

Abstract: This study aimed to characterize the honeys of Babors Kabylia through sensory, melissopalynological and physico-chemical parameters. Thirty samples of honey produced in this region were collected over a period of two years and analyzed. All the samples presented physico-chemical parameters in conformity with legislation on honey quality, with few exceptions, linked mainly to beekeeping management. The pollen spectrum revealed a great diversity with 96 pollen types. The main pollen types were spontaneous specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 40 publications
10
28
0
1
Order By: Relevance
“…pH levels ranged from 3.880 ± 0.015 to 4.373 ± 0.011, with a mean pH value of 4.088 ± 0.127. These values are close to those reported for honey samples from the Kabylia area (Algeria) [43], along with certain Tunisian honey [48], Spanish samples [1], and Malaysian honey [49].…”
Section: Physicochemical Propertiessupporting
confidence: 87%
“…pH levels ranged from 3.880 ± 0.015 to 4.373 ± 0.011, with a mean pH value of 4.088 ± 0.127. These values are close to those reported for honey samples from the Kabylia area (Algeria) [43], along with certain Tunisian honey [48], Spanish samples [1], and Malaysian honey [49].…”
Section: Physicochemical Propertiessupporting
confidence: 87%
“…The diastase index is defined as the number of milliliters of 1% starch solution that was processed in dextrin for one hour at 45 °C at an optimum pH of amylase containing 1 g honey. The diastase activity was determined by the Schade procedure [ 26 , 81 ]. The absorbance was measured at a wavelength of 660 nm using a Perkin Elmer UV-VIS LAMBDA EZ201.…”
Section: Methodsmentioning
confidence: 99%
“…Pesticides may cause changes in the endocrine system [ 20 ], the reproductive system [ 21 , 22 , 23 ], and the nervous system [ 24 , 25 ]. The concentration of mineral elements in honey can be determined by inductively coupled plasma mass spectrometry (ICP-MS) or by atomic absorption spectrometry (AAS) [ 26 , 27 ]. Honey can be contaminated with pesticides from agricultural practices and beekeeping.…”
Section: Introductionmentioning
confidence: 99%
“…The analytical methods, the sensory evaluation of honey can complement the confirmation of the botanical origin, establish sensory profiles for monofloral honey, verify quality, among others [ 118 ], since various studies have observed differences in the characteristics of honeys according to their floral and geographical origin [ 50 , 60 , 119 , 120 , 121 ]…”
Section: The Color Of the Honey And Phenolic Compoundsmentioning
confidence: 99%